(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In today’s digital age, social media has transformed from a communication tool into a major influencer of consumer behavior. This paper examines how platforms like TikTok, Instagram, and YouTube shape Gen Z’s purchasing decisions through influencer marketing, personalized algorithms, and social validation. By exploring recent studies, this article highlights the growing power of online communities and digital trends in shaping the modern consumer mindset.